Ras-Induced miR-146a and 193a Target Jmjd6 to Regulate Melanoma Progression - Anelli, Viviana; Ordas, Anita; Kneitz, Susanne; Sagredo, Leonel Munoz; Gourain, Victor; Schartl, Manfred; Meijer, Annemarie H.; Mione, Marina (Frontiers in Genetics, 2018)
Ras genes are among the most commonly mutated genes in human cancer; yet our understanding of their oncogenic activity at the molecular mechanistic level is incomplete. To identify downstream events that mediate ras-induced cellular transformation in vivo, we analyzed global microRNA expression in three different models of Ras-induction and tumor formation in zebrafish. Six microRNAs were found increased in Ras-induced melanoma, glioma and in an inducible model of ubiquitous Ras expression. The upregulation of the microRNAs depended on the activation of the ERK and AKT pathways and to a lesser extent, on mTOR signaling. Three Ras-induced microRNAs (miR-146a, 146b, and 193a) target Jmjd6, inducing downregulation of its mRNA and protein levels at the onset of Ras expression. However, at later stages of melanoma progression, Jmjd6 levels were elevated. The dynamic of Jmjd6 levels during progression of melanoma in the zebrafish model suggests that upregulation of the microRNAs targeting Jmjd6 may be part of an anti-cancer response. Indeed, triple transgenic fish engineered to express a microRNA-resistant Jmjd6 from the onset of melanoma have increased tumor burden, higher infiltration of leukocytes and shorter melanoma-free survival. The connection miR146/193-JMJD6 is conserved in human melanoma, indicating that the up-regulation of Jmjd6 is a critical event in melanoma progression.